Characterization of the clientele attended in a Psychosocial Care Center - alcohol and drugs - Eliany Nazaré Oliveira; Maria Wanessa Pereira Silva; Sara Cordeiro Eloia; Francisca Waldiane Pereira Mororó; Gleisson Ferreira Lima; Manuelle Maria Marques Matias (Rev Rene)
This documentary and retrospective study aimed to analyze the profile of the clientele attended in the Psychosocial Care Center Alcohol and Other Drugs from Sobral, Ceará, Brazil in 2010, based on 300 records. Males predominated with 75% (n=225), with age ranging from 11 to 29 years old with 44.3% (n=133), single with 49% (n=147), and with elementary school 45.7% (n=137). The most commonly used drug among men was crack, 31.3% (n=94), and among women, tobacco, 12% (n=36). The losses associated with dependence, are mostly related to the family, with 31.3% (n=94). The highlight to crack requires changes in the care process implemented in institutions. One should remain alert to these new profiles related to chemical dependency, so that quality and integral care can be offered to this clientele.